(untitled) (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
This paper represents an attempt to draw the attention on the great potential, still incompletely explored in the Romanian archaeology, represented by this category of finds from the point of view of identifying contacts between individuals and communities, often with very different cultural foundation, in the framework of the Roman world. Based on an assessment of the old publications presenting funerary contexts from two cities from the western coast of the Black Sea, Tomis (Constanța) and Callatis (Mangalia), with glass vessels as part of their grave goods, the authors will discuss the presence of this category of archaeological material on these two sites, with a special focus on the category of unguentaria or toilet-bottles.